Study of ABO System and Multiple Sclerosis disease in Iraq - Soud, Shemaa A.; Al-Rubae’i, Salwa H.N. (Iraqi Journal of Science, 2022)
Multiple sclerosis (MS) is one of an autoimmune condition with uncertain etiopathology. According to new data, ABO system had played a role in the development and understanding numerous diseases. Lower level of 25-hydroxy vitamin D3 (25-OHD3) is considered as a risk factor for MS. The aims of this study is to identify the role of blood group distribution on the levels of parathyroid hormone (PTH), 25-OHD3, total calcium, inorganic phosphorus and total magnesium on MS patients. Additionally, we assessed the relation between Expanded Disability Status Scale (EDSS) and study parameters in patients. The Study included 107 patients with MS were distributed in to four groups according to their blood group (A, B, AB, and O). Additionally, 124 apparently healthy individuals as control group. Tukey analysis was showed the level of 25-OHD3 in patients with B+ was significant decrease than O+ and A+ patients group (P≤0.05). Furthermore, EDSS was negatively correlated with 25-OHD3 (P≤0.05) in B+ and O+ patient groups. Through this study, ABO group may be consider as a risk factor for MS susceptibility as another interesting variable.